Survey for Sensor-Cloud System from Business Process Outsourcing Perspective - JeongYeon Kim (International Journal of Distributed Sensor Networks)
Cloud computing is a new IT trend to meet the new business requirements such as business agility and operational efficiency with business process outsourcing (BPO). Sensor-Cloud infrastructure is the extended form of cloud computing to manage the sensors which are scattered throughout the network. Several benefits of adopting cloud computing including cost saving, high scalability, and business risk reductions also can be applied to sensor data collection. As a first investment for new technology, we analyze IT managers' feedbacks to identify the most important factors of decision making for cloud platform adoption and IT outsourcing. Even though the technological motivation is persuasive in Korean IT market, survey results show that the cost efficiency is the most important for cloud platform adoption. Also surveys reveal that IT service consumers have difficulties understanding complicated service contracts and data sharing issues with infrastructure providers, which serve as main blockers of adopting cloud computing.